Evolving Treatment Options for Spinal Pain: Balancing Innovation and Affordability in Regenerative Medicine - Annu H. Navani; Sudhir A. Diwan; Douglas P. Beall; Edward S. Rubin; Ahmed I. Anwar; Alan D. Kaye (Current Pain and Headache Reports, 2026)
Abstract Purpose of Review Regenerative approaches for treating spinal pain hold great clinical promise but have the potential to disrupt healthcare upending the cost paradigm of pharmacologic care or interventional procedures. Regenerative approaches have higher upfront costs but may offer long-lasting, even curative benefits. In today’s healthcare system, it is important to understand the cost-effectiveness of regenerative approaches using mesenchymal stem cells (MSC), platelet-rich plasma (PRP), and other biologics. This narrative review explored the costs of these procedures for treating spinal pain, but since this specific indication is not currently approved for clinical use in the United States, cost data were sparse. Recent Findings This study was based on a narrative review and data obtained from the literature and available to the authors from a scientific session. While regenerative medicine is approved for certain indications, it has not yet been approved for use to treat painful spinal conditions, although there is evidence that it is a safe and effective procedure in this setting. In fact, PRP approaches to other musculoskeletal painful conditions are approved and increasing, according to Medicare. When compared to fusion surgery, MSC treatment of discogenic disease cost approximately $11,000 in the United States compared to two years of epidural spinal injections costing approximately $900 each; the regenerative approaches offered better pain reduction (66% vs. 35% to 51%). Spinal fusion surgery runs $79,595 to $105,657 according to current procedural terminology. Once regenerative approaches for the spine are approved, there may be more data to provide greater insight into cost-effectiveness analyses. Summary There is a paucity of cost data and since these procedures are off label, these figures are subject to change and may vary regionally. Regenerative medicine offers the potential to greatly advance the treatment of back pain, but in today’s cost-conscious healthcare system, cost considerations must be weighed along with efficacy and safety data.